El sincretismo como forma de preservación de las ideas. Historiografía de la iconografía virreinal - Maqueira Yamasaki, Ángeles (2016)
This article is a historiographical study about iconography in Colonial Art and Architecture. The main bias of this study would be the idea of syncretism and cultural hybridization between Pre-Hispanic and Christian spirituality brought by the Spaniards. The research aims to outline the relationship between the Pre-Hispanic figures and those resulting from our territory evangelization, highlighting correspondences, mixtures and combinations of some Christian icons with those representative of the Andean mythology. Everything was within a context in which Baroque Art allows such type of complexity and diversity.